Conflict between communities and PT Ani palm oil company in Nilas Hamlet, Sebatih Village, Landak Regency - Bahari, Yohanes; Warneri, Warneri; Aminuyati, Aminuyati (Edelweiss Applied Science and Technology, 2025)
This research aims to analyze the conflict between the community and the palm oil company PT ANI in Nilas Hamlet, Sebatih Village, Landak Regency. The research approach used was descriptive qualitative with a case study method. The research informants consisted of the village head, hamlet head, customary administrators, ordinary people, and partnership farmers, determined purposively. Data collection was conducted through in-depth interviews with data collection tools and interview guidelines. Data analysis involved data reduction, data presentation, and conclusion drawing. The study findings reveal a conflict involving PT ANI, with identified parties including the community, interest groups, and customary administrators. This conflict, rooted in agrarian, interest, and structural issues, stems from changes in traditional socio-economic structures towards a community pattern favoring capitalism. Spanning from 1995 to 2022, the conflict represents a culmination of various factors. Resolution efforts have predominantly relied on customary and positive legal approaches.